Identifying the Drivers of PM2.5Concentration Changes between December 2019 and December 2020 in South Korea - Kim, Soontae; Bae, Minah; Kim, Eunhye; Son, Kyuwon; Kang, Yoon Hee; Kim, Yunha; You, Seunghee; Kim, Byeong Uk; Kim, Hyun Cheol (Journal of Korean Society for Atmospheric Environment, 2021)
The observed monthly mean PM2.5concentration in South Korea during December 2020 has decreased by 2.3 μg/m3, compared to that during the same month in the previous year, but the drivers of the change have been veiled yet. This study quantitatively examines the roles of the potential drivers of the PM2.5decrease during December 2020. Air quality simulations for December 2019 and December 2020 show that the change in meteorology conditions have increased the PM2.5concentrations by 1.4 μg/m3in South Korea, but the changes in the Northeast Asian emissions have decreased the PM2.5concentrations by 3.7 μg/m3in the country. In addition, foreign emission impact on the nationwide PM2.5concentrations estimated from a set of the sensitivity simulations with the Community Multi-scale Air Quality model and adjusted with the surface observations in China has increased by 1.9 μg/m3in December 2020, compared to that for December 2019. It means that the upwind foreign emission condition was not helpful in the downwind PM2.5decrease. On the contrary, the domestic impact has decreased by 4.2 μg/m3over the country, which compensated the increase in the foreign impact for the month. The observed monthly mean NO2concentrations have decreased by 5% and 8% for South Korea and the Seoul Metropolitan Area, respectively, compared to the same month in 2019. When a simple observation-based emission adjustment was applied, a 5% decrease in the national total NOxemissions for the month was estimated. The causality of NO2decrease still needs further investigations, but the seasonal PM2.5management and social distancing after the COVID-19 re-outbreak at the end of November might have led to the reduction in the anthropogenic emissions (i.e., NOx) and thus the PM2.5concentrations during the month.
Keywords: Emissions; Foreign and domestic impacts; Meteorology; PM2.5; Social distancing